Food Intake Monitoring System for Mobile Devices - Mendi, Şekip Engin; Özyavuz, Öcal; Pekesen, Emrah; Bayrak, Coşkun (IEEE, 345 E 47Th St, New York, Ny 10017 Usa, 2013)
In this paper, we introduce a real-time food intake monitoring system for mobile devices. The proposed system gets acceleration data from the sensor placed on the wrist of the user during a meal. The data is then sent to the mobile device via Bluetooth. The system analyses patterns between the motion profile and bite actions by first filtering the data to remove noise effects and then identifying the peaks. Based on detecting peaks, real-time feedback regarding eating trends such as total number of bites, bites-taken rate and eating speed is provided to the user. If the eating is too fast, the system warns the user in the form of both audio and text. The mobile application is implemented on the Android Platform and tested on a subject successfully. The proposed system offers an affordable quick solution that can be used in any place where eating happens. It can help people who are obese or with other eating disorders by monitoring consumption of food intake to control their eating rate in real-time.
Keywords: Engineering, Electrical & Electronic